2010
DOI: 10.5194/hess-14-1963-2010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the hydrologic response of a mesoscale Andean watershed to changes in land use patterns for environmental planning

Abstract: Abstract. A multidisciplinary approach is followed for analysis of the effect of changes in land use patterns on the hydrologic response of the Vergara watershed (4340 km 2 ) located in central Chile. Probable future land use scenarios were generated using heuristic rules and logistic regression models, in order to identify and represent the main pressure on the watershed, namely forestation of extensive areas used for agriculture with rapid growing exotic species. The hydrologic response of the watershed was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 53 publications
(53 reference statements)
0
20
0
1
Order By: Relevance
“…The study sites correspond to the lower Itata (36°12′–37°16′ and 71°00′–73°10′) (Link et al ., ) and the Vergara (37°29′–38°14′ and 71°36′–73°20′) (Stehr et al ., ) rivers, located in Central Chile. These reaches have lengths of 32 and 20 km, average altitudes of 68 and 27 masl, catchment areas equal to 11 290 and 4340 km 2 and Strahler orders at the study reach outlet of 6 and 5, respectively.…”
Section: Study Site and Field Instrumentationmentioning
confidence: 99%
“…The study sites correspond to the lower Itata (36°12′–37°16′ and 71°00′–73°10′) (Link et al ., ) and the Vergara (37°29′–38°14′ and 71°36′–73°20′) (Stehr et al ., ) rivers, located in Central Chile. These reaches have lengths of 32 and 20 km, average altitudes of 68 and 27 masl, catchment areas equal to 11 290 and 4340 km 2 and Strahler orders at the study reach outlet of 6 and 5, respectively.…”
Section: Study Site and Field Instrumentationmentioning
confidence: 99%
“…The authors showed that information from short‐term glacio‐meteorological experiments within the region is indispensable for the estimation of parameter values in distributed, physically oriented glacio‐hydrological models. Meanwhile, studies with application of conceptual (Melo et al ., ; Vicuña et al ., , ) or physically oriented but semi‐distributed (Stehr et al ., , , ) hydrological models are relatively abundant in the Central Andes of Chile. Because streamflow data are relatively available, but field measurements represent a considerable financial and logistical effort, such models have often been favoured over more complex distributed models (Sivapalan, ), in spite of the risk of overparametrization resulting, for example, in the adequate fit between observed and modelled streamflow but overall in a less realistic simulation of catchment behaviour (Seibert and McDonnell, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, remote sensing provides a promising opportunity to enhance the assessment and monitoring of the spatial and temporal variability of different variables involved in the precipitation-runoff processes in areas where data availability for hydrological modelling is scarce (Simic et al, 2004;Boegh et al, 2004;Melesse et al, 2007;Montzka et al, 2008;Milzowa et al, 2009, Er-Raki et al, 2010Stehr et al, 2009Stehr et al, , 2010.…”
mentioning
confidence: 99%